Investigating EFL Students’ Perception of AI- Powered Learning Assistance - Kurnia Febianti; Ricky Yakob; Yoga Pratama (Smart Edu Center, 2025)
This study investigates EFL learners’ perceptions of the integration of artificial intelligence (AI) into English language learning. The rapid advancement of AI has significantly influenced various aspects of social life, including education, where AI-based tools are increasingly utilized to support learning activities. This research aims to explore students’ perspectives on the effectiveness, benefits, and challenges of AI applications in English learning. A descriptive was employed, using a Likert-scale closed-ended questionnaire and open-ended questions as instruments for data collection. The participants consisted of students from the English Department of STKIP Muhammadiyah Pagaralam. The findings reveal that students generally have positive perceptions of AI applications in learning English. Most respondents agree that AI facilitates the learning process, enhances efficiency, and supports the development of language skills through features such as translation, grammar checking, and pronunciation assistance. However, several challenges were also identified, including inaccurate outputs and limited accessibility due to poor internet connectivity. In conclusion, AI applications serve as effective tools in EFL learning by accelerating the learning process and improving learning efficiency, although technical and reliability issues remain important considerations for their optimal use.